Mainstreaming Nutrition in Poverty Reduction Strategy Papers : What Does It Take? A Review of the Early Experience - Shekar, Meera; Lee, Yi-Kyoung (World Bank, Washington, DC, 2013)
This paper reviews 40 full poverty reduction strategy papers (PRSPs) with regard to whether these strategy papers (1) recognize under-nutrition as a development problem in the country, (2) whether they use nutrition information for poverty analysis, and (3) whether the PRSP includes specific nutrition activities (policies, strategies, and programs) to deal with the unique nutrition problems in each country. The review shows that three quarters of the PRSPs recognize that under-nutrition is a development problem that leads to loss of human capital and/or productivity. Also, many PRSPs, either explicitly or implicitly, include country nutrition profiles in their poverty analysis. Consequently, a majority of PRSPs include strategies and specific actions to mitigate the effects of malnutrition. However, there appears to be little prioritization or sequencing of proposed actions. More importantly, the strategies and actions included in PRSPs often do not reflect an appropriate response to the nature of the nutrition problem in the country. In a quarter of countries with macronutrient deficiencies and about 40% of countries with micronutrient deficiencies, the PRSPs fail to address these two problems. Moreover, tackling nutrition issues requires greater institutional capacity and budget allocations than currently seem to exist. Gross mismatches between the causes of malnutrition and responses to the nutrition problem inevitably lead to a lack of impact and a waste of resources, which will further contribute to the marginalization of nutrition in future PRSPs.